Early Childhood Teachers' Understanding and Practice of Inclusive Curriculum: A Mixed Method Study in Bandung - Sudarti Sudarti; Susan Maulani; Agus Ruswandi (MASI Mandiri Edukasi, 2026)
This study investigates Early Childhood Education (ECE) teachers’ understanding and practice of inclusive curriculum implementation, and examines the role of training and collaboration in enhancing teacher competence. Employing a concurrent triangulation mixed-method design, quantitative and qualitative data were collected through questionnaires, in-depth interviews, observations, and document analysis. Simple random sampling was used for the survey, while purposive sampling identified key informants with direct experience in inclusive practices. The findings indicate that teachers demonstrate a relatively good conceptual understanding of inclusive principles, particularly in recognizing children’s diversity, applying child-centered approaches, and valuing collaboration with parents and support staff. However, a significant gap persists between conceptual understanding and classroom practice, especially in adaptive lesson planning and differentiated instruction. Continuous professional training contributes positively to improving pedagogical competence, although institutional support and professional supervision remain limited. Collaboration among teachers, parents, and support staff is identified as a critical factor in fostering inclusive learning environments. Despite growing attention to inclusive education, prior studies have largely focused on teachers’ perceptions rather than examining how such understanding is enacted in practice, particularly through the combined influence of training and collaborative support. This study highlights the need for sustained, reflective, practice-based training and strengthened professional partnerships to ensure effective, sustainable, inclusive curriculum implementation in ECE contexts.